Enhancing Thermostability and Organic Solvent Tolerance of ω‐Transaminase through Global Incorporation of Fluorotyrosine. Issue 5 (11th March 2014) - Deepankumar, Kanagavel; Shon, Minsu; Nadarajan, Saravanan Prabhu; Shin, Giyoung; Mathew, Sam; Ayyadurai, Niraikulam; Kim, Byung‐Gee; Choi, Sei‐Hyun; Lee, Sang‐Hyeup; Yun, Hyungdon
Abstract Here, we have utilized the incorporation of non‐canonical amino acids as a tool kit to improve enzyme properties for organic synthesis applications. The global incorporation of 3‐fluorotyrosine (FY) into ω‐transaminase (ω‐TA) to give ω‐TA[FY] enhanced the thermostability and organic solvent tolerance without altering substrate specificity and enantioselectivity. Moreover, ω‐TA[FY] was able to completely convert 25 mM of acetophenone into (S)‐1‐phenylethylamine (ee>99%) in the presence of 20% DMSO (v/v) which is ∼2‐fold higher when compared to wild‐type ω‐TA. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>